Development and testing of new force fields for molecular dynamics simulations - (:unkn) unknown (Nazarbayev University, 2013)
The objective of this research is to develop and test new polarizable atomic force fields (FFs) for “in-vacuum” and “in-water” non-bonded interactions based on AMBER ff99SB-ILDN force fields, improved by inclusion of new terms. FFs parameter optimization will be done using our set of molecular crystals with crystallographic data from the Cambridge Structural Database and sublimation/solvation thermodynamics characteristics from various sources.
Keywords: first research week; molecular dynamics; atomic force fields